Perlindungan Hukum Kepada Korban Tindak Pemalsuan Data Pribadi Nasabah Perbankan Ditinjau Dari Undang-Undang Nomor 27 Tahun 2022 Tentang Perlindungan Data Pribadi - Ario Rambang Pangestu (Kampus Akademik Publiser, 2024)
Legal Protection for Victims of Fraudulent Personal Data of Banking Customers in View of Law Number 27 of 2022 concerning Personal Data Protection. Criminal responsibility is a form of determining whether a person who is a suspect or perpetrator of a criminal act can be held responsible for a criminal act that has occurred, in other words, criminal responsibility is a form that determines whether a person can be acquitted or even punished. Criminal responsibility also covers the perpetrator's previous actions, which can be seen from these actions whether there were other actions or just one, as well as whether the perpetrator did it alone or together with other parties, whether they helped directly or indirectly. Criminal acts in the banking sector according to Law No. 7 of 1992, concerning banking, Law Number 10 of 1998. As is known, criminal acts in the banking sector are a form of criminal acts in the economic sector. Criminal acts in the banking sector are carried out using banks as a means and target. In general, it can be said that the forms of criminal acts are divided into 2 (two), namely crimes and violations. Crimes are some of the actions that are prohibited and punishable by crime, whoever commits them. Basically, criminal acts are regulated in the second book of the Criminal Code.